Women and the Social Resilience in Post-Conflict Areas of Lampung - Hasanah, Uswatun (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
Lampung Province has several areas which are allegedly conflict-prone areas that have disturbed the social life of the community and have also endangered the lives and property of the victims. In this case, women have a very crucial role, especially in creating social resilience after conflict. This research examines women's strategic role in building post-conflict social resilience in Lampung Province. This research was qualitative research with interviews, observation, and documentation as data collection techniques and source triangulation to test the validity of the data. The results of the research showed that women have a very crucial role in developing post-conflict social resilience in Lampung Province, namely the strategic role of women in the family includes active participation in improving the quality of life and the family economy, educating and instilling the values of tolerance and awareness of diversity in children and increasing insight and awareness of the role of women through participation in social and religious activities. Furthermore, the role of women in society is to support and play an active role in the implementation of social activities, increase the frequency of togetherness activities as a forum for interacting and communicating with each other in differences as well as holding and playing an active role in social activities that are neutral in nature, without being based on ethnic or religious elements. In conclusion, by optimizing the role of women, social resilience in society can be created.